Analisis Integrasi Audit Siklus Persediaan Dengan Manajemen Risiko Untuk Mencegah Terjadinya Kecurangan Dan Kehilangan Aset - Noor Zulaika; Aldi Alamsa; Masyuri, Masyuri (Journal of Economic and Business Advancement, 2026)
Inventory management represents one of the most critical areas exposed to fraud and asset loss due to its high value and operational complexity. This study examines the integration of inventory cycle auditing and risk management as a strategic approach to preventing fraud and safeguarding organizational assets. The analysis highlights that risk-based inventory audits enable auditors to focus on vulnerable areas where misstatements, theft, and procedural weaknesses are most likely to occur. Risk management frameworks support this process by systematically identifying, assessing, and mitigating inventory-related risks throughout procurement, storage, and distribution stages. The role of internal control systems and accounting information systems is emphasized as a key factor in enhancing audit effectiveness and ensuring reliable inventory data. Findings from relevant literature indicate that organizations implementing integrated audit and risk management practices experience stronger internal control performance and reduced incidents of inventory losses. This integration positions auditing not merely as a detection mechanism but as a preventive and value-adding function within inventory governance. Consequently, the alignment between inventory auditing and risk management contributes significantly to sustainable asset protection and organizational accountability.